2021
DOI: 10.1111/ijfs.15364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound‐vacuum‐assisted extraction on bioactive properties of pitaya (Hylocereus undatus)

Abstract: This study aimed to investigate the effect of ultrasound-assisted extraction under vacuum on bioactive properties of peel and flesh of pitaya fruit, and also compare with sonication under atmosphere condition using the principal component analysis (PCA). Vacuum sonication exhibited better results for total phenolic (56.78-71.54 mg GAE per 100 g for peel; 11.03-17.92 mg GAE per 100 g for flesh) and total flavonoid (95.33-115.71 mg QE per 100 g for peel; 13.26-19.36 mg QE per 100 g for flesh) amounts. DPPH free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In reference to the antioxidant activity of pitahaya-flesh flour, the values obtained in this study were lower than those reported by Hernandez-Ramos et al [6], who stated that ABTS and FRAP values of H. ocamponis flesh were 20.09 and 11.64 mM Trolox Equivalent/g, respectively. In a similar study, Uslu and Özcan [32] found that the antioxidant capacity of pitahaya flesh (H. undatus) measured with DPPH assay was 24 mM/g. Concerning the antioxidant capacity of peel extracts, Bassey et al [33] reported that the extracts obtained from the peel of red pitahaya var.…”
Section: Antioxidant Propertiesmentioning
confidence: 78%
“…In reference to the antioxidant activity of pitahaya-flesh flour, the values obtained in this study were lower than those reported by Hernandez-Ramos et al [6], who stated that ABTS and FRAP values of H. ocamponis flesh were 20.09 and 11.64 mM Trolox Equivalent/g, respectively. In a similar study, Uslu and Özcan [32] found that the antioxidant capacity of pitahaya flesh (H. undatus) measured with DPPH assay was 24 mM/g. Concerning the antioxidant capacity of peel extracts, Bassey et al [33] reported that the extracts obtained from the peel of red pitahaya var.…”
Section: Antioxidant Propertiesmentioning
confidence: 78%
“…Phenolic compounds found both in the pulp and in the peel of different dragon fruit species are not only used as food supplements but also as additives in medicine, cosmetics, and the food industry in order to increase the bioavailability of the product, prolonging its shelf-life [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the extraction of bioactive compounds, traditional applications such as distillation, maceration, decoction, and compression were commonly used for years, although these techniques would take up more time, energy, solvent, and labor (Chemat et al, 2017; Ojha et al, 2020; Rojas et al, 2021). One of the alternative extraction methods is ultrasound‐assisted extraction which increases yields and eliminates the disadvantages of conventional technologies (Moreira et al, 2019; Uslu & Özcan, 2021). The use of acoustic energy breaks down cell walls and creates microchannels in the tissues, thus improving the solvent penetration into the food matrix.…”
Section: Introductionmentioning
confidence: 99%